Cellulolytic Actinomycetes isolated from soil in Bukit Duabelas National Park, Jambi - ATIT KANTI (Society for Indonesian Biodiversity, 2005)
The objective of study was to investigate the enzymatic activities of cellulolytic Actinomycetes. The soil sample was collected from Bukit Duabelas National Park, Jambi. Actinomycetes was isolated by Casein Agar Medium, and its cellulolytic capacity was determined by measuring the activity of CMC-ase. Two isolates of cellulolytic Actinomycetes belonged to genus Streptomyces were isolated. The CMCase activity was 7.7 unit and 13.4 unit for isolate I and isolate II respectively. The Km of isolate I and isolate II were 1.356x 10-3 and 1.595x10-3 (% b/v) respectively. Vmaks of isolate I and II was 1.658 x10-4 and 6.166x 10-4 Î¼g glukosa/mL enzyme /minute, respectively.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: Actinomyctes, Streptomyces, Celulolytic, Bukit Dua Belas National Park.